Assistance in the Development of Digital Marketing in Kebangsaan Tourism Village Wonorejo - Fondina Gusriza; Joko Mijiarto (Future Science, 2022)
Kebangsaan Tourism Village is one of the buffer villages located next to the Baluran National Park. This tourist village has enormous tourism potential to be developed. The management has used promotions through Instagram social media since July 2018, but Instagram social media has only been managed for 5 months as evidenced by the last post on December 16, 2018. Kebangsaan Tourism Village also has a website with the name desawistakebangsaanwonorejo.id, but it is no longer managed so it cannot be accessed by tourists. It can be concluded that the promotion and marketing conditions of the Kebangsaan Tourism Village have stopped and are no longer carried out. The purpose of this service is training and promotion assistance by utilizing the website and social media. The method used in this service is training and mentoring. Based on the results of the training and mentoring carried out, it shows that there is an increased understanding of social media management. The management can manage websites with the name www.dewikebangsaan. This website is using as a promotion tools and sharing information related to tourism activities in the Kebangsaan Tourism Village. The management has knowledge of Instagram content, complete information on the main page, and efforts to increase insight with paid advertising.